Validation of the aMAP score to predict hepatocellular carcinoma development in a cohort of alcohol‐related cirrhosis patients. Issue 2 (12th March 2022) - Liu, Ken; Yip, Terry C. F.; Masson, Steven; Fateen, Waleed; Schwantes‐An, Tae‐Hwi; McCaughan, Geoffrey W.; Morgan, Timothy R.; Aithal, Guruprasad P.; Seth, Devanshi
Abstract: Background and Aims: The aMAP score was recently devised to predict hepatocellular carcinoma (HCC) development. However, its performance was not tested in alcohol‐related cirrhosis (ALC). We aimed to validate the aMAP score in a cohort of ALC patients. Method: Study participants with ALC from a prior genome‐wide association study were included. All participants had a history of high alcohol consumption. Cirrhosis was defined clinically, using fibroscan and/or histology. Patients were followed until the last liver imaging, HCC, liver transplantation (LT) or death with the latter two adjusted as competing risks. Results: A total of 269 ALC patients were included: male (72.5%), Caucasian (98.9%), median age 56 years, and median Child‐Pugh score 7. The median aMAP score was 60: 12.3% low‐risk, 35.3% medium‐risk and 52.4% high‐risk. After a median follow‐up of 41 months, 14 patients developed HCC, 27 received LT and 104 died. The aMAP score predicted HCC development (hazard ratio 1.12 per point increase, P < .001) with good separation of cumulative incidence function between risk groups. The area under the time‐dependent receiver operating characteristics curve for predicting HCC development was 0.83 at 1 year and 0.82 at 5 years which was similar to ADRESS‐HCC and Veterans Affairs Healthcare System scores respectively. Conclusions: We validated the excellent performance of the aMAP score in ALC and affirm its applicability across wider aetiologies. Abstract : The aMAP score, which is calculated from age, sex, albumin, bilirubin, and platelet count, has been shown to accurately predict the risk of hepatocellular carcinoma (HCC) in patients with chronic liver disease (mainly viral hepatitis). We validated its usefulness in a cohort of patients with alcohol‐related cirrhosis (ALC) and showed it performed similarly to other HCC risk scores. This easy‐to‐use score can help identify ALC patients at high risk of HCC who may need closer attention during surveillance.